PENGARUH PEMANGKASAN DAN PENAMBAHAN GIBERELIN (GA3) TERHADAP LAMA WAKTU PEMBENTUKAN TUNAS DAN KUNCUP BUNGA TANAMAN MAWAR (Rosa sp) - Listijani Suhargo; Y. Sri Wulan Manuhara (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1995)
The effect of cutting and adding gibberellin on the duration of stem and flower bud forming of Rosa sp had been done. This research purpose to shorthen the duration of stem and flower bud forming. The research sample were Rose plant with yellow colour and the same length and number of branches. The cutting was done on 0 cm, 5 cm, and 10 cm from the apex. In this research, we used gibberellins with 50 ppm and 100 ppm concentrations and as a control we used aquadest. The result showed that the best treatment to shorthen the duration of stem bud forming were the cutting 10 cm from the apex and with adding of gibberellin on 100 ppm concentration. And the best treatment to shorthen the duration of flower bud forming were with the cutting on 10 cm from the apex and with adding of gibberellins on 50 ppm concentration.